2000
DOI: 10.1002/1098-2795(200012)57:4<311::aid-mrd2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Caprine pregnancy-associated glycoproteins (PAG): Their cloning, expression, and evolutionary relationship to other PAG

Abstract: Pregnancy‐associated glycoproteins (PAG) are structurally related to aspartic proteinases and belong to an extensive, rapidly evolving family of recently duplicated genes expressed in the placentas of artiodactyl species. The aim of the present study was to clone PAG from the goat, study their temporal and cell‐specific expression, and determine their phylogenetic relationship to PAG from other species. RT‐PCR was used to generate PAG cDNA from pooled placental RNA obtained between days 45 and 115 of pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 36 publications
4
43
0
1
Order By: Relevance
“…It is novel in that the studies were completed at a stage of gestation that has yet to be examined. Our study confirmed one of the most interesting features of PAGs, the switching of gene expression [13,21]. Some PAG are thought to be expressed first and then to be replaced at a later time by others.…”
Section: Discussionsupporting
confidence: 83%
“…It is novel in that the studies were completed at a stage of gestation that has yet to be examined. Our study confirmed one of the most interesting features of PAGs, the switching of gene expression [13,21]. Some PAG are thought to be expressed first and then to be replaced at a later time by others.…”
Section: Discussionsupporting
confidence: 83%
“…The PAGs represent a large gene family and are expressed in a host of other species such as cattle, sheep, goats, etc. (Xie et al, 1991;Garbayo et al, 2000;Green et al, 2000). Proteins somewhat related to this class are expressed in rodents (Chen et al, 2001) and equids (Green et al, 1998(Green et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are synthesized by the mono-and binucleate trophoblastic cells and released into maternal blood starting from first weeks of pregnancy until delivery. PAGs are already detectable in placental tissue around the time of implantation Garbayo et al, 2000;Green et al, 2000;Wooding et al, 2005).…”
Section: Structural and Biochemical Differentiation In A Range Of Pagmentioning
confidence: 99%
“…From a scientific and economic side it was a progression in the breeding of those animals. PAGs are synthesized in the outer epithelial cell layer (chorion/trophectoderm) of the placenta Green et al, 1998;Garbayo et al, 2000). Part of the molecules traffics into maternal blood and milk (Tainturier et al, 1996;Gajewski et al, 1999;Metelo et al, 2002;Lopez-Gatius et al, 2007;Gajewski et al, 2008a;Gajewski et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%